Pain Drawings Improve Subgrouping of Low Back Pain Patients. Issue 3 (23rd June 2016) - Hüllemann, Philipp; Keller, Thomas; Kabelitz, Maria; Freynhagen, Rainer; Tölle, Thomas; Baron, Ralf
Abstract: Background: Subgrouping of low back pain (LBP) patients may be improved when pain drawings are combined with the painDETECT (PD‐Q) questionnaire. We hypothesized that (1) different LBP subgroups determined by their pain radiation show different clinical patterns and (2) the occurrence of neuropathic symptoms depends on pain radiation. Methods: A total of 19, 263 acute (< 6 weeks' duration), subacute (6 to 12 weeks), and chronic (> 3 months) LBP patients were allocated prospectively into 4 groups based on the location of pain drawings on a manikin and compared regarding neuropathic pain components, functionality, depression, pain intensity, and surgical interventions. All items were investigated at baseline and follow‐up visits. Group I was composed of patients with axial LBP without radiating pain; group II, LBP with radiation into the thigh; group III, LBP with radiation into the shank; and group IV, LBP with radiation into the feet. Side‐dependent pain radiation was assessed additionally. Results: Depression, functionality, and pain intensity showed no clinically relevant differences, whereas PD‐Q scores and the probability to rate positive for neuropathic pain increased with more distally radiating pain. Surgery and medication intake were most frequent in group IV. Follow‐up analyses showed that only axial LBP became more neuropathic, whereas pain intensity decreased over time. Conclusions: Radicular patterns of pain drawings in LBP patients indicate severe pain conditions with the most neuropathic components, while axial LBP has the fewest. For the categorization of LBP, pain drawings help explain the underlying mechanism of pain, which might further improve mechanism‐based treatment when used in clinical routines and research.